STRATEGI PEMBELAJARAN AFEKTIF UNTUK MENINGKATKAN PENDIDIKAN MASA DEPAN - Tabita Mutia Tambunan; Surya Ganda Pasaribu; Damayanti Nababan (CV. Denasya Smart Publisher, 2024)
Affective learning strategies aim to expose students to problem situations, so that they can make decisions based on parts that are considered quality. The research used by the author is a literature study or called the literature review method, which is sourced from books, journals, and websites that discuss affective learning to improve morals through student character or attitudes, for future student provision. Religious education in schools plays an important role in the formation and development of students' attitudes and morals, one of which is to fulfill spiritual needs and mindsets. Challenges such as a dense curriculum require effective religious learning strategies to instill religious values that can be applied in everyday life. These strategies should also help students understand themselves to control emotions and form strong characters. Increased student motivation can be achieved through verbal rewards, test scores as a motivator for success, and rewards. Fun learning will make learners more understandable, active and motivated. In the context of values and attitudes education, learning strategies should include the organization of materials as well as clear and measurable objectives. Value and attitude education is very important in shaping individual character in accordance with norms, laws, religion, and academics.